Kajian Yuridis Peraturan Mahkamah Agung Republik Indonesia Nomor 12 Tahun 2016 Tentang Tata Cara Penyelesaian Perkara Pelanggaran Lalu Lintas di Wilayah Hukum Pengadilan Negeri Wonosari - Wahyuni Tri Atmojo (Universitas Janabadra, 2019)
This research is motivated by the completion of electronic based traffic cases online e tilang. But in its application there are problems that arise in Police Agencies, Courts and Prosecutors. One of them is the limited period of validity of the BRIVA code so that violators must request the BRIVA code again on the Traffic investigator. The settlement of Traffic matters under the rule of the Supreme Court of the Republic of Indonesia Perma. No. 12 of 2016 was conducted with a trial without the presence of a violator verstek so the offender could not submit a defense of the article which was deemed. The main problem that will be answered by this research is the application of the Supreme Court of the Republic of Indonesia regulation number 12 of 2016 concerning procedures for settlement of cases Traffic in the Wonosari district court of law. Legal remedies adopted by the violator against the settlement process of the Traffic case based on the Supreme Court of the Republic of Indonesia regulation number 12 of 2016 in the jurisdiction of the procurement of Wonosari jurisdiction. And the obstacles faced by law enforcement officials in implementing the Supreme Court regulation of the Republic of Indonesia number 12 of 2016 in the jurisdiction of the procurement of Wonosari jurisdiction. The research was carried out with a normative juridical approach considering that what would be revealed was a matter of written rules, legal issues from law enforcement officers, and a view of the applicable criminal procedural law theory. The Object is done by interviewing parties who are considered to be able to provide information in accordance with the object needed and literature study. The results showed that the Supreme Court of Indonesia's Republic of Indonesia regulation number 12 of 2016 concerning the procedures for the settlement of traffic cases was applied with an integrated electronic based system e tilang which was presented without the presence of violators verstek. Legal remedies carried out by filing resistance against objections to decisions or stipulations that seize independence, not decisions on the amount of the fine. Objections were filed on that day. The obstacle faced is the BRIVA code which has a time limit, there is no uniformity of ticket penalties throughout the Courts in Indonesia, and and it still requires less efficient time in the prosecutor's office for violators whose BRIVA code has expired and must firstask the traffic investigator.